S131 Deficiency mutations of α1-antitrypsin differentially affect folding, function and polymerisation. (12th November 2015) - Haq, I; Irving, JA; Saleh, AD; Dron, L; Regan-Mochrie, GL; Motamedi-Shad, N; Hurst, JR; Lomas, DA; Gooptu, B
Abstract : Misfolding, polymerisation and defective secretion of functional α1 -antitrypsin underlie the predispositions to severe liver and lung disease in α1 -antitrypsin deficiency. We have identified a novel (Ala336Pro, Baghdad) deficiency variant and characterised it relative to the wild-type (M) and common severe Z (Glu342Lys) variant. The index case is a homozygous individual of consangineous parentage. Absolute levels of circulating α1 -antitrypsin were in the moderate deficiency range but the biochemical phenotype could not be clearly classified by standard methods. Moreover the majority was polymerised, i.e. functionally inactive, and the purified monomer was only 37% active relative to the wild-type 'M' variant. Together these resulted in 85–95% loss-of-function, a similarly severe functional deficiency to that of ZZ homozygotes. Biochemical, biophysical and computational studies further defined the molecular basis of this functional deficiency. These demonstrated that native Ala336Pro α1 -antitrypsin could adopt the polymerogenic intermediate conformation and polymerised more readily not only than M α1 -antitrypsin but also the severe Z variant. Nevertheless folding was far less impaired in Ala336Pro α1 -antitrypsin than in the Z variant. The data therefore indicate partitions between the contribution of the 'breach' (site of Z mutation) and 'shutter' (Ala336Pro) regions of strand 5A to folding and to polymerisation mechanisms. Moreover the findings demonstrate that in these variants, folding efficiency does not correlate directly with the tendency to polymerise in vitro or in vivo . They therefore differentiate generalised misfolding from polymerisation tendencies in missense variants of α1 -antitrypsin. Clinically they further support the need to quantify loss-of-function in α1 -antitrypsin deficiency to individualise patient care.